PENGARUH PENINGKATAN DANA BEASISWA BIDIKMISI TERHADAP HASIL BELAJAR MAHASISWA DI JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Nurul Fadilla (Universitas Negeri Padang, 2018)
In taking a quality education and education to a higher level, a large fee is needed. The government in dealing with this problem, provides assistance in the form of a scholarship program. One of the scholarships provided by the government is the Bidikmisi scholarship. In early 2017 the government increased the bidikmisi scholarship fund received by students. This is so that students can improve their learning outcomes. This study aims to determine whether there is an effect of increasing bidikmisi scholarship funds on student learning outcomes in the Department of Economic Education, Faculty of Economics, Padang State University. This study uses a comparative causal type of research. The population in this study were students in the Department of Economic Education, Faculty of Economics, Padang State University, in 2014, 2015 and 2016. The sampling technique in this study used proportional sampling technique. The data used is the Achievement Index (IP) value of students before and after increasing the Bidikmisi scholarship fund from the Economics Education Department FE-UNP. The results of this study indicate that the increase in bidikmisi scholarship funds does not affect the learning outcomes of students in the Economics Education Department FE-UNP. Based on the results of the research, suggestions that can be given are (1) To the institutions and parties who provide bidikmisi scholarships it is advisable to be able to control the use of bidikmisi scholarships so that the scholarship funds can be used for academic needs so as to support the increase in student outcomes by asking for learning outcomes students to the Vice Dean 1 or Academic Advisor; (2) The parties involved with the Bidikmisi scholarship at UNP are advised to follow up on the implementation of bidikmisi scholarship financial misuse through periodic 1 (one) periodic reports; (3) Students who receive bidikmisi scholarships are advised to manage scholarship funds that are well received, in accordance with the purpose of scholarships that can support improvements in learning outcomes; (4) Further researchers are advised to continue and refine this research to be able to produce a more complete picture of the effect of Bidikmisi scholarship fund enhancement on student learning outcomes or the behavior of parents and students who receive bidikmisi scholarships. Keywords: Bidikmisi Scholarship, Learning Outcomes